1994
DOI: 10.1161/01.cir.90.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in QT interval dispersion by successful thrombolytic therapy in acute myocardial infarction. TEAM-2 Study Investigators.

Abstract: Successful thrombolysis is associated with less QTd and JTd in post-AMI patients. The results are equally significant when either QT or JT is used for analysis. These data support the hypothesis that QTd after AMI depends on reperfusion status as well as infarct site and size. Reduction in QTd and its corresponding risk of ventricular arrhythmia may be mechanisms of benefit of thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
90
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(107 citation statements)
references
References 59 publications
13
90
2
2
Order By: Relevance
“…We found that QT dispersion in the chronic phase was also larger in patients with anterior infarction, as was the case in the acute phase. 12,19) This suggests that QT dispersion should be assessed while taking into consideration the location of the infarct as well as the time of measurement, as pointed out by Glancy, et al 4) The present study also showed that QT dispersion increased as the infarct became larger. It is not clear whether a larger infarct can directly cause an increase in QT dispersion or is associated with wall motion abnormalities that lead to a secondary increase in QT dispersion, but QT dispersion was suggested to be increased in patients with extensive myocardial infarction.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found that QT dispersion in the chronic phase was also larger in patients with anterior infarction, as was the case in the acute phase. 12,19) This suggests that QT dispersion should be assessed while taking into consideration the location of the infarct as well as the time of measurement, as pointed out by Glancy, et al 4) The present study also showed that QT dispersion increased as the infarct became larger. It is not clear whether a larger infarct can directly cause an increase in QT dispersion or is associated with wall motion abnormalities that lead to a secondary increase in QT dispersion, but QT dispersion was suggested to be increased in patients with extensive myocardial infarction.…”
Section: Discussionsupporting
confidence: 74%
“…Raev, et al 10) investigated the relationship between QT dispersion and infarct size at four days after onset, and noted that QT dispersion was smaller and wall motion abnormalities were milder in patients with inferior infarction than in those with anterior infarction. In a study assessing the relationship between coronary lesions and QT dispersion at nine days after infarction, Moreno, et al 12) found that QT dispersion was significantly larger in patients with lesions of the left anterior descending coronary artery than in those with lesions of the left circumflex coronary artery or right coronary artery. They also found that a reduction in infarct size after reperfusion caused a decrease in QT dispersion, indicating that dispersion was dependent on both the location and size of the infarct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 On the other hand, it has been shown that QTD decreases subsequent to successful thrombolysis in acute myocardial infarction. 10 Recently, it has been reported that QTD obtained by exercise ECG increases the diagnostic reliability of ST-segment changes. 11,12 We planned this study to test whether, in addition to QTD and QTcD, the QT dispersion ratio (QTDR), which is shown to be more specific than QTcD for ventricular arrhythmias, 13 and differences between exercise and rest QTcD and QTDR, which are first evaluated, increase the diagnostic accuracy of ECG in women.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The values were higher in the early hours, but decreased after thrombolytic therapy. (3) Greater QT dispersion is associated with severe ventricular arrhythmias TEAM-2 Study Investigators have done a study on Reduction in QT interval dispersion by successful thrombolytic therapy in acute myocardial infarction 29 . They studied 244 patients with acute myocardial infarction (AMI) who were thrombolysed at an average of 2.6 hours after symptom onset.…”
Section: Discussionmentioning
confidence: 99%